Educational Thoughts of Swami Vivekananda and its Futuristic Relevance – A Study - Nisha Bharadwaj; Pradeep M. D., (International Journal of Management, Technology and Social Sciences (IJMTS), 2023)
Purpose: To review the Indian education system in the 21st Century to find lacunas and to develop a holistic approach to disseminate knowledge and impart skills as proposed by Swami Vivekananda in his educational philosophy of man-making in the light of character-building ideologies. Research Design: Descriptive and Analytical research design is used for the study through SWOC analysis by using secondary data including research articles published in international journals and books which are available for search in the google scholar database. Result/Outcome/findings of the Study: The study identifies the gap in modern education which is a hurdle for the holistic development of youth. The study emphasizes man-making by developing Values, Character, and Manifestation of the inner self. The outcome recommends the holistic approach by connecting the gist of the educational ideology of Swami Vivekananda and the crux of the New Education Policy 2020. Originality/Value: The paper reviews the educational ideologies proposed by Swami Vivekananda are connected to the crux of NEP-2020 with the SWOC analysis framework. The value of the philosophical thoughts of Swami Vivekananda matches with the NEP-2020 policy document to a greater extent. An earnest attempt has been done with the basis of relevant sources to suit the educational philosophy of Swami Vivekananda to the NEP-2020 policy. Paper type: Descriptive/Analytical Study